The latest video projectors can fit inside tiny cameras or cellphones yet still produce big pictures [Little Gizmo, Big Picture]. - Lincoln, J. (IEEE spectrum)
The latest video projectors can fit inside tiny cameras or cellphones yet still produce big pictures. What a pico projector does is simple: It takes a digital image and sends it out as a beam of light, creating an image that's much bigger than the originating device. Every pico projector needs chips to process and decode the image data for the hardware, a light source, typically LEDs or laser diodes, and mirrors and optics, to direct and focus the image.